2021
DOI: 10.4103/jfmpc.jfmpc_1004_21
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on psychological and academic performance of medical students in Saudi Arabia

Abstract: Background and Objectives: The COVID-19 pandemic affected the mental health and psychosocial conditions of everyone worldwide according to the WHO. Public health emergencies affect college students and are expressed as anxiety, worry, and fear. The aim of this study was to assess the impact of COVID-19 on the psychological health and performance of medical students. Design and Settings: A cross-sectional study using an online survey was done. Participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…Another point to consider is that academic performance is an important confounding variable between stress and EI. 2 Cajachagua Castro et al did not address this in their analysis, which we believe to be a significant limitation to their research. 1 Studies have demonstrated that higher grade point averages are associated with increased anxiety levels in students.…”
Section: Dear Editormentioning
confidence: 86%
See 1 more Smart Citation
“…Another point to consider is that academic performance is an important confounding variable between stress and EI. 2 Cajachagua Castro et al did not address this in their analysis, which we believe to be a significant limitation to their research. 1 Studies have demonstrated that higher grade point averages are associated with increased anxiety levels in students.…”
Section: Dear Editormentioning
confidence: 86%
“…1 Studies have demonstrated that higher grade point averages are associated with increased anxiety levels in students. 2 With the authors failing to report or control for the academic achievement levels of the participants, 1 the validity of the findings are questionable. We recommend that future studies should capture academic performance data and appropriately incorporate it into multivariate models.We appreciate the authors use of multiple frameworks to investigate EI, stress coping and concern over returning to face-to-face learning.…”
mentioning
confidence: 99%
“…In terms of personal factors, sex has been significantly associated with anxiety and depression among medical students in many studies, with most reporting that women have a higher prevalence of anxiety [ 16 , 19 , 43 , 48 , 65 , 87 , 98 , 111 , 114 , 115 , 120 , 132 , 135 , 137 , 145 , 155 ] and depression [ 16 , 19 , 43 , 48 , 65 , 69 , 114 , 115 , 120 , 131 , 135 ]. Only one study reported that male students had a high risk of anxiety [ 32 ], and one study reported that male students had a high risk of depressive symptoms [ 164 ].…”
Section: Discussionmentioning
confidence: 99%
“…A past study cites a positive correlation between anxiety and high academic achievement. [ 15 ] Similarly, there has been another study on the adaptations of students to online education and the associated difficulties. [ 15 16 ] The primary prevention focuses on persons susceptible to developing mental disorders and consequences due to their bio-psycho-social characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…[ 15 ] Similarly, there has been another study on the adaptations of students to online education and the associated difficulties. [ 15 16 ] The primary prevention focuses on persons susceptible to developing mental disorders and consequences due to their bio-psycho-social characteristics. [ 17 ] The current study is significant since it focuses on students enrolled in various undergraduate health-related programs in Medicine, Dental, Applied Medical Sciences, Pharmacy, and Nursing colleges and the student’s overall well-being.…”
Section: Introductionmentioning
confidence: 99%